2005
DOI: 10.1037/0893-3200.19.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal pathways linking family factors and sibling relationship qualities to adolescent substance use and sexual risk behaviors.

Abstract: This 3-wave, 5-year longitudinal study tested the contributions of family contextual factors and sibling relationship qualities to younger siblings' substance use, sexual risk behaviors, pregnancy, and sexually transmitted disease. More than 220 non-White families participated (67% Latino and 33% African American), all of which involved a younger sibling (133 girls and 89 boys; mean age = 13.6 years at Time 1) and an older sister (mean age = 17 years at Time 1). Results from structural equation latent growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 33 publications
9
83
0
2
Order By: Relevance
“…Much progress has occurred during the past two decades to enhance the description and explanation of sexual risk behaviors in both community and clinical samples of adolescents. Particularly important analytic strategies have included structural equation modeling (SEM) to test causal models among distal and proximal influences on indicators of adolescent sexual behavior [42,43]. However, other significant research questions related to the expression of sexual risk behavior by adolescents have received less research attention.…”
Section: Identifying Patterns Of Riskmentioning
confidence: 99%
“…Much progress has occurred during the past two decades to enhance the description and explanation of sexual risk behaviors in both community and clinical samples of adolescents. Particularly important analytic strategies have included structural equation modeling (SEM) to test causal models among distal and proximal influences on indicators of adolescent sexual behavior [42,43]. However, other significant research questions related to the expression of sexual risk behavior by adolescents have received less research attention.…”
Section: Identifying Patterns Of Riskmentioning
confidence: 99%
“…This is particularly interesting because siblings can be thought of as a special subset of peers (Clayton & Lacy, 1982) and are among the longest lasting relationships that most people have (Cafarro & Conn-Cafarro, 2005). Moreover, siblings serve as important contexts for individual development (East & Khoo, 2005; Patterson, 1986). Healthy sibling relationships provide companionship, support, and guidance which are associated with healthier outcomes later in life (Dunn, 2005).…”
mentioning
confidence: 99%
“…They also shape the nature of encounters that take place (Rubin & Rubin, 1992), influencing not only the topics selected for conversation but the intimacy with which they are discussed (Graham et al, 1993). Further, because motives shape what is achieved during interactions, understanding what drives sibling communication may help account for why some siblings communicate in ways that serve purposes, such as inhibiting risk behaviors in teenage brothers or sisters (East & Khoo, 2005) or facilitating beneficial communication behaviors (e.g., reminiscence) in later life (Nussbaum et al, 2000). Finally, knowing why individuals communicate with their siblings might help explain why some siblings derive greater pleasure from their relationships than others, as certain communication motives (e.g., pleasure, inclusion, and affection) have demonstrated positive associations with communication satisfaction (Rubin, Perse, & Barbato, 1988).…”
Section: Interpersonal Communication Motivesmentioning
confidence: 93%
“…Although themes of intimacy and closeness as functions of ethnicity could be fruitfully explored by communication scholars, we believe it would be interesting to explore how other aspects of sibling relationships may be enacted by members of different ethnic communities such as the communication of affection, the performance of relational maintenance, and the interpretation of verbal aggression. Given that a recent study found that close bonds with an older sister can buffer at-risk Latino and African American youth from susceptibility to drug and alcohol abuse (East & Khoo, 2005), researchers could also examine the communicative mechanisms through which children and young adults reduce sibling vulnerability to risky behaviors.…”
Section: Implications For Future Researchmentioning
confidence: 99%